Potential of Flavonoids as Promising Phytotherapeutic Agents to Combat Multidrug-Resistant Infections - Pathak, Deepika; Mazumder, Avijit (Current Pharmaceutical Biotechnology, 2024)
Background: Considering the limited number of current effective treatments, Multidrug- Resistant (MDR) illnesses have grown to be a serious concern to public health. It has become necessary to look for new antimicrobial drugs because of the emergence of resistance to numerous kinds of antibiotics. The use of flavonoids is one phytotherapeutic strategy that has been researched as a potential remedy for this issue. Secondary plant compounds called flavonoids have been found to have an antibacterial effect against resistant microorganisms. Objective: This review seeks to give readers a glimpse into contemporary studies on flavonoids' potential to fight MDR infections. Methods: A systematic search was conducted on electronic databases (PubMed, Scopus, and Google Scholar) using relevant keywords such as flavonoids, MDR infections, antimicrobial activity, and resistance microbes. Studies that investigated the antimicrobial activity of flavonoids against resistant microbes were included in this review. Results: Most research found that flavonoids have antibacterial efficacy against resistant microorganisms, and some also showed that they have synergistic benefits with traditional antibiotics. The flavonoids quercetin, kaempferol, apigenin, and luteolin were the most often investigated ones. According to research, flavonoids affect microbial gene expression, inhibit microbial enzymes, and disrupt the integrity of microbial cell membranes. Additionally, a few studies have noted the flavonoids' low toxicity and safety. Conclusion: For the treatment of infections that are resistant to many drugs, flavonoids constitute a promising class of phytotherapeutic agents. To develop flavonoid-based treatment methods for treating MDR illnesses and assess the potential of flavonoids as adjuvants to conventional antimicrobial drugs, more study is required.
Keywords: treatment